STRATEGI PENGENTASAN KEMISKINAN DALAM PERSPEKTIF ISLAM - Cantika, Sri Budi (Journal of Innovation in Business and Economics, 2013)
Islamic perspective views poverty as a result of several structural reasons, namely environmental damage due to human activity (Surah Ar Rum: 41); ignorance and the miserliness of the wealthy (Surah Al 'Imran: 180); tyranny, exploitation, and oppression of some people over others (Surah At-Tawbah: 34); political, bureaucracy, and economic power concentration in one hand (Surah Al Qasas; 1-88); poverty arising from external factors such as natural disaster or civil wars that drastically changed the rich become poor (Surah Saba ': 14-15). Islam proposes some strategies in order to reduce poverty which covers: 1) Promoting economic growth that benefits to the wider community (pro-poor growth); 2) Encouraging the construction of national budget which protect majority of people (pro-poor budgeting); 3) Assisting infrastructure development that aids many people (pro-poor infrastructure); 4) Establishing proper basic public services in favor of the broader community (pro-poor public services); and 5) Pushing equity and income distribution policies that prioritize the poor (pro-poor income distribution).